Methylation of an alpha-foetoprotein gene intragenic site modulates gene activity. - Opdecamp, K (1992)
By comparing the methylation pattern of Mspl/Hpall sites in the 5' region of the mouse alpha-foetoprotein (AFP) gene of different cells (hepatoma cells, foetal and adult liver, fibroblasts), we found a correlation between gene expression and unmethylation of a site located in the first intron of the gene. Other sites did not show this correlation. In transfection experiments of unmethylated and methylated AFP-CAT chimeric constructions, we then showed that methylation of the intronic site negatively modulates expression of CAT activity. We also found that a DNA segment centered on this site binds nuclear proteins; however methylation did not affect protein binding.